Nano-TiO2(B) coated LiMn2O4 as cathode materials for lithium-ion batteries at elevated temperatures. (20th February 2015) - Shang, Yesheng; Lin, Xiujing; Lu, Xu; Huang, Tao; Yu, Aishui
Abstract: In this study, nano-TiO2 (B) coated LiMn2 O4 was prepared via a two-step method, combining a hydrothermal method with electrostatic attraction. By adjusting the sintering time, porous and dense nano-TiO2 (B) coating structure were formed on the surface of LiMn2 O4 particles. Electrochemical test results showed that 2 wt.% porous TiO2 (B) coated LiMn2 O4 exhibited highest capacity retention at 77.4% after 300 cycles at 55 °C and the best rate capability. Inductively coupled plasma spectroscopy(ICP), charge and discharge curves and electrochemical impedance spectroscopy (EIS) results revealed that the improved electrochemical performances was due to the suppression of the undesired SEI film, as well as suppression of Mn dissolution at the cathode and reduced polarization.